TACTICAL BEHAVIOR IN SOCCER SMALL-SIDED GAMES: INFLUENCE OF TACTICAL KNOWLEDGE AND NUMERICAL SUPERIORITY - Gilbson Moreira Praça; Cicero Luciano Alves Costa; Frederico Falconi Costa; André Gustavo Pereira de Andrade; Mauro Heleno Chagas e Juan Pablo Greco (Journal of Physical Education)
ABSTRACT This study investigated the influence of procedural tactical knowledge (PTK) and numerical superiority on the tactical behavior of soccer players during small-sided games. Eighteen male soccer players were divided into six teams, of which three showed higher PTK, and three lower PTK. Data was collected over six days, with two 4-minute sets of small-sided games held by group. Tactical behavior was assessed through FUT-SAT. Two-way ANOVA (group x game) was used for data analysis. In the group factor, only width and length principles showed difference, being more frequent in the lower PTK group. As for game factor, 3x3 SSG presented higher penetration incidence, while in the 4x3 SSG players performed more actions of unity (offensive and defensive), defensive coverage and balance. It is concluded that PTK levels have lower influence on tactical behavior than on game situation.